Digital Marketing Communication Strategy in Building Brand Awareness at Riverside Car Wash - Susi Marni; Nani Cahyani; Febriyantina Istiara; Ruruh Aris Setya Wibawa; Rahayusriasih H (Journal of Creative Power and Ambition (JCPA), 2026)
The development of digital technology has brought significant changes in the business world, including in the motor vehicle maintenance service industry. The use of digital media, especially social media platforms, is one of the main strategies in marketing communication to reach consumers more widely, quickly, and interactively. This study aims to analyze the digital marketing communication strategies applied by Riverside Car Wash in building brand image and increasing brand awareness in the digital era. The research method used is a descriptive qualitative approach, with data collection techniques through in-depth interviews, participatory observation, and digital documentation. Data analysis was carried out using thematic analysis techniques to identify communication patterns and the effectiveness of the digital strategies applied. The results of the study show that Riverside Car Wash implements a consistent digital marketing communication strategy through the use of social media such as Instagram, TikTok, and official websites. Content strategies that highlight visual before-after wash results, vehicle maintenance education, and active interaction with customers have been proven to increase engagement and strengthen a company's brand image. The main challenges found include limited human resources in the field of digital marketing and inconsistency in upload schedules. Overall, Riverside Car Wash's implementation of digital marketing communication strategies has proven to be effective in strengthening brand image, increasing brand awareness, and building customer loyalty.